(untitled) (Journal of Hama University, 2024)
Escherichia coli is considered one of the most important threats to the health of birds and a major cause of economic losses in broiler farms due to the death it causes, low conversion efficiency, and delayed growth. The danger of these germs comes in light of the indiscriminate use of antibiotics to treat them, in addition to the emergence of resistance to these antibiotics, which may reach humans. Therefore, this study aims to investigate Escherichia coli infection in some broiler farms in Tartous Governorate, isolate and confirm the infection, and study the effectiveness of some antibiotics used to treat it. Samples were collected during the period from 2/2/2023 to 12/2/2023 from different areas: (Al-Hamidiyah, Al-Raqma, Al-Safliyya, Beit Shihan, Zahiwiyah, Al-Qumsiyeh, Bilwaza, Baghlikh, Shubat, and Khirbet Amoudi). Symptoms were recorded a pathological autopsy was performed and samples were grown in nutritious soup and incubated at 37°C then cultured on specific media to diagnose the presence of Escherichia coli bacteria and susceptibility tests to some antibiotics were performed. The results showed a high rate of resistance which reached 100% to erythromycin, 90% to chloramphenicol and doxycycline 83.33% to azithromycin 70% to fosfomycin, 66.66% to gentamycin and 60% to colistin. It is inferred from this that Escherichia coli was sensitive to colistin and gentamycin and that their effectiveness reached a rate of 30% followed by fosfomycin with a sensitivity of (23.33%) then azithromycin, doxycycline, and chloramphenicol where the effectiveness of each reached a rate of (10%). The statistical analysis showed significant differences between the studied antibiotics as colistin outperformed the rest of the antibiotics with a high statistical significance of (2.743), followed by gentamycin with a statistical significance (2.833), then the antibiotic fosfomycin with a statistical significance (2.952), the antibiotic doxycycline with a statistical significance (3.438), then arythromycin. With statistical significance (3.550), chloramphenicol with statistical significance (3.863), then azithromycin with statistical significance (3.993).This indicates the presence of high levels of bacterial resistance to most of the antibiotics studied, resulting from the indiscriminate use of these antibiotics in treatment processes, and the necessity of working to increase awareness of their responsible use, with national interest in this, which reduces the risk of this resistance being transmitted to humans while monitoring its effects in practical application And testing increased effectiveness through partnership and synergy. Keywords: Escherichia coli, chickens, effectiveness, antibiotics.